IMPLEMENTATION OF THE FMADM ALGORITHM AND SAW METHOD IN BOARDING HOUSE SEARCH - Baun, Sindy Cristine; Purnomo, Hindriyanto Dwi (Jurnal Teknik Informatika (Jutif), 2024)
Current developments have made many developments, one of which is boarding houses. There are many immigrants from outside the region who want to study at Nusa Cendana University, Kupang City but have difficulty in finding a boarding house because of many considerations such as what facilities are provided by the boarding house owner. The lack of information on boarding house occupancy makes it difficult for prospective residents who are looking for boarding houses to obtain information about boarding houses with the criteria of each boarding house, to overcome this problem the Fuzzy Multi Attribute Decision Making (FMADM) Algorithm and Simple Additive Weighting (SAW) Method are needed with the aim of making it easier for female students to find boarding houses that suit their wishes and the best around Nusa Cendana University, Kupang, NTT. After analysis, the FMADM algorithm turned out to be able to help determine the weight of the value of each criterion in finding the best boarding house and also the SAW method can be implemented very well so that it can make it easier to add up the weight value of each criterion by doing alternative ranking. The results of the research that have been studied show that using the FMADM algorithm and the SAW method can produce the best alternative as the best solution from other alternatives, with Kost Putri Bilm@t being the best alternative out of 100 other alternatives studied with a ranking value of 4.106667. With the best alternative obtained, it shows that by using the FMADM algorithm and the SAW method, the number of samples used is large, the level of validity also often increases.